Theoretical foundations of continuity in teaching mathematics - Madi Alyia (Theoretical Hypotheses and Empirical Results, 2023)
The continuity between primary school and Primary School has been widely debated in recent times. Continuity provides, on the one hand, for the transfer of children to school whose general development and level of Education meets the requirements of school education, on the other hand, for the active use of the knowledge, skills, acquired by pupils in school for the further comprehensive development of students [1]. The first data on teaching simple calculations to children, the first data can be seen in the historical data of the countries of the Ancient East. The development of metep mathematical knowledge of mathematics was significantly influenced by the ancient Greek culture of mathematics. In the V century BC, the trade revolution began to teach simple calculations and practical geometry in elementary schools.